A snapshot of the Late Jurassic Western Tethys seafloor composition and morphology provided by the geochemistry of pelitic sediments (Corsica, Central Alps and Northern Apennines). (15th December 2013) - Bracciali, L.; Pandolfi, L.; Rocchi, S.
Abstract The chemical composition of fine‐grained siliciclastic sediments is a powerful tool in provenance studies, either as a complement to other whole rock/single grain methods, or as a stand‐alone method when other techniques are not applicable, and particularly in those cases where the coarser sediment fractions are not available or the regional‐scale geologic framework is lost due major successive tectonic events. A comprehensive geochemical investigation of pelites from the post‐rift deposits of the Ligurian‐Piedmont ocean (sampled in tectonic units of the Alpine‐Apennine orogen: Balagne Nappe, Corsica; Tuscan Nappe and Internal Ligurian units, Northern Apennines; Err‐Platta units, Central Alps) has identified for the first time a major mafic‐ultramafic input immediately following rifting. Key trace element ratios (e.g. LaN/YbN < 10; avg. Eu/Eu* = 0.73 ± 0.06, 1SD; Th/(Cr + Ni + V) < 0.03) show that the pelitic siliciclastic layers intercalated in the Radiolarite Formation (the first post‐rift deposits) are systematically enriched in a mafic‐ultramafic source component compared with the younger post rift sediments (Calpionella Limestone and Palombini Shale). Such a peculiar chemical fingerprint is interpreted as the result of erosion and distribution across the whole basin (even to continental domains) of intraoceanic ophiolitic debris by turbidity and bottom currents sweeping the sea floor at the time of deposition of the Radiolarite Formation. Exhumed mantle and gabbroic‐basaltic rocks exposed at the morphologically articulated seafloor of the slow‐spreading Ligurian‐Piedmont ocean were available to erosion during the whole time‐span of the deposition of the Radiolarite Formation, whilst they became progressivey subordinate as a source as the basin floor was progressively covered by the siliciclastic input from the developing passive continental margins.